Bisulfite‐free PCDHGB7 methylation in urine enables early noninvasive detection of urothelial carcinoma - Zhicong Yang; Qing Chen; Shihua Dong; Peng Xu; Zhanrui Mao; Yaping Dong; Wei Li; Wenxuan Li; Yang Han; Lihe Dai; Gehong Dong; Yong Zhang; et al. (Bioengineering & Translational Medicine)
Abstract Urothelial carcinomas (UCs) are the fourth most common male malignancies. However, currently implemented detection methods for UC are usually invasive and/or show passable sensitivity and specificity. An accurate, practical, and effective approach is urgently needed for UC clinical detection. Based on the observation that PCDHGB7 was hypermethylated in UC, we developed a bisulfite‐free quantitative polymerase chain reaction (qPCR)‐based PCDHGB7 evaluation to enable urine for UC noninvasive detection. A total of 887 urine samples from UC/benign diseases of the urinary system (BUD) patients between 2022 and 2023 were included. All collected samples were divided into training and validation sets in a 2:1 ratio based on the order of patient enrollment. Results showed that hypermethylated PCDHGB7 exhibited excellent sensitivity of 87.3% (95% CI: 80.7%–92.3%) and specificity of 91.0% (95% CI: 84.8%–95.3%) in efficiently distinguishing UC from BUD patients in the validation set, which is highly consistent with its performance in the training set. Moreover, PCDHGB7 hypermethylation showed promising potential in identifying sessile UC tumors or cases that might be missed in clinical detection and outperformed standard urine cytology in detecting bladder cancer (82.1% vs. 34.5%), ureter cancer (78.1% vs. 34.4%), and renal pelvis cancer (90.9% vs. 22.7%). Overall, bisulfite‐free qPCR‐based PCDHGB7 evaluation in urine provided a noninvasive, easy‐to‐perform, and effective way for UC early detection.